Analysis of Environmental Management Accounting Implementation in RSUD Dr. Saiful Anwar Malang - Izdiharningrum Ghina Sary; Helianti Utami; Endang Sri Andayani (AIBPM Publisher, 2022)
This review plans to examine the application of environmental management accounting (EMA) in RSUD Dr. Saiful Anwar Malang. It includes an analysis of the performance of RSUD Dr. Saiful Anwar Malang in terms of the environment, monetary information, and physical information of the application of EMA in hospitals. The examination method was descriptive qualitative. Information assortment procedures are perception, interviews, and documented information. The findings indicate that the hospital has implemented EMA based on the EMA framework) and environmental cost classification. In addition, the hospital has carried out waste management so well that there were no external costs. For the application of environmental accounting, the hospital has included environmental costs and general accounting theories and principles. Keywords: Environmental Cost, Environmental Management Accounting (EMA), RSUD Dr. Saiful Anwar Malang, Monetary Environmental Management Accounting (MEMA), Physical Environmental Management Accounting (PEMA)